Lattice Boltzmann method fundamentals and engineering applications with computer codes - Mohamad,A. A. (Abdulmajeed A.); SpringerLink (Online service). (London Springer, 2011)
Lattice Boltzmann Method introduces the lattice Boltzmann method (LBM) for solving transport phenomena - flow, heat and mass transfer - in a systematic way. Providing explanatory computer codes throughout the book, the author guides readers through many practical examples, such as: flow in isothermal and non-isothermal lid driven cavities; flow over obstacles; forced flow through a heated channel; conjugate forced convection; and natural convection. Diffusion and advection-diffusion equations are discussed with applications and examples, and complete computer codes accompany the coverage of single and multi-relaxation-time methods. Although the codes are written in FORTRAN, they can be easily translated to other languages, such as C++. The codes can also be extended with little effort to multi-phase and multi-physics, if the reader knows the physics of the problem. Readers with some experience of advanced mathematics and physics will find Lattice Boltzmann Method a useful and easy-to-follow text. It has been written for those who are interested in learning and applying the LBM to engineering and industrial problems and it can also serve as a textbook for advanced undergraduate or graduate students who are studying computational transport phenomena.
1 Introduction and Kinetic of Particles -- 2. The Boltzmann Equation -- 3. The Diffusion Equation -- 4. Advection-Diffusion Problems -- 5. Isothermal Incompressible Fluid Flow -- 6. Non-isothermal Incompressible Fluid Flow -- 7. Multi-relaxation Schemes -- 8. Complex Flows.
Electronic reproduction.
Keywords: Electronic book; Fluid mechanics -- Mathematical models; Mechanics, Applied -- Mathematical models